Hristiyan fundamentalizmi - Albayrak, Hafize Şule (My University, 2006)
Amerika Birleşik Devleti’ndeki hristiyan fundamentalizminin kökeni 19.yy.’a dayanır. 20.yy.’ın ilk çeyreğinde somut şeklini alan hareket, kurduğu okullar, basım yayım kuruluşları, hastahaneler, üniversiteler ve kiliseler vasıtasıyla toplumsal zeminini güçlendirmiş ve siyasi planda varlık göstermekten çekinmemiştir. Başlıca fundamentalizm olgusunu; ardından Amerika’daki Protestan fundamentalizmini incelediğimiz bu çalışmada, fundamentalist inanç esasları ortaya konduktan sonra Amerika’daki tarihsel arka plana değinilmiştir. Çalışmamız, ayrıca Amerika’daki fundamentalistlerin aile, cinsiyet, siyaset ve diğer din mensuplarıyla ilgili görüşlerini de incelemektedir. Yahudilere yaklaşımlarıyla dikkat çeken fundamentalistler, Müslüman Filistinliler’e karşı İsrail’in yanında olmakla ön plana çıkmışlardır.

The origins of the christian fundamentalism in the United States are found in the nineteenth-century. In the first quarter of the twentieth-century, the movement took its concrete form. The social base of fundamentalism was strengthened by forming fundamentalist schools, churches, universities, hospitals and media (televisions, magazines, radio programmes…). When the fundamentalist movement had enough power, it didn’t hesitate to enter the political arena. This study that focuses on the Protestant fundamentalism in the United States analyzes the fundamentalist beliefs, doctrines and also the historical background of fundamentalism in the United States. Moreover, it examines the arguments of the fundamentalists in America about family, gender, politics and the members of other religions. One of the most distinguishing feature of fundamentalists in America is their approach toward Jews. They support Israil without any provision and take the position against muslims.
Keywords: Din Sosyolojisi; Hristiyanlık